2021
DOI: 10.4014/jmb.2109.09012
|View full text |Cite
|
Sign up to set email alerts
|

Picropodophyllotoxin Induces G1 Cell Cycle Arrest and Apoptosis in Human Colorectal Cancer Cells via ROS Generation and Activation of p38 MAPK Signaling Pathway

Abstract: Picropodophyllotoxin (PPT), an epimer of podophyllotoxin, is derived from the roots of Podophyllum hexandrum and exerts various biological effects, including anti-proliferation activity. However, the effect of PPT on colorectal cancer cells and the associated cellular mechanisms have not been studied. In the present study, we explored the anticancer activity of PPT and its underlying mechanisms in HCT116 cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to monitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…99 Moreover, Lee found that PPP could also induce G1 arrest and apoptosis in human colorectal cancer cells via ROS generation and activation of the p38 MAPK signalling pathway. 100…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…99 Moreover, Lee found that PPP could also induce G1 arrest and apoptosis in human colorectal cancer cells via ROS generation and activation of the p38 MAPK signalling pathway. 100…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…AC45971100, also known as fluometuron, is an immune modulator that may exert its effects by inhibiting mitochondrial enzyme dihydroorotate dehydrogenase and effectively suppressing the growth of breast cancer cells [ 42 ]. NSC35468, or Podophyllotoxin bromide, is less commonly reported but has been suggested in literature to induce mitochondrial inner membrane depolarization and caspase-dependent apoptosis in colorectal cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown that, in the presence of melatonin, the phosphorylation of JNK and of p44/42 was diminished, whereas an increase in the phosphorylation of p38 was noted. Increased phosphorylation of p38 MAPK has been related with cell death [ 27 ]. In addition, low levels of phosphorylated JNK and p44/42 have been related with diminished cell proliferation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%